The root canal shaping ability of WaveOne and Reciproc versus ProTaper Universal and Mtwo rotary NiTi systems - Ahmed S Abu Haimed; Tariq S Abuhaimed; Paul E Dummer; Susan T Bryant (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to compare the root canal shaping ability of two reciprocating instruments: WaveOne and Reciproc versus two rotary instruments - ProTaper Universal (PTU) and Mtwo. Materials and Methods: A total of 160 simulated root canals in resin blocks were constructed with two curvatures located at two positions creating four different combinations: 20°/8 mm, 20°/12 mm, 40°/8 mm, and 40°/12 mm. Canals were prepared using continuous rotation (PTU and Mtwo) or reciprocating (WaveOne and Reciproc) instruments according to the manufacturer's recommendations. Each system was used to prepare 10 canals of each shape. Each file or a set of files was used to prepare one canal. Using Image Analysis Software, pre- and post-instrumentation matching images were superimposed and analyzed for canal width and transportation. Instrument fractures, time of preparation, and change in working length were also recorded. The effect of instrument and canal type on shaping ability were analyzed using two-way ANOVA test followed by post hoc Pearson Chi-square test and sum of squares test at level of significance 5%. Results: The largest mean canal width and transportation values were associated with the Mtwo system (P < 0.001) and 40°/8 mm canals (P < 0.001). Canal aberrations were limited to rotary instruments mainly in canals with 40° curves. The reciprocating instruments prepared canals significantly faster than continuous rotation systems (P < 0.001). Conclusions: Continuous rotation and reciprocating files were safe and maintained the original canal anatomy. However, continuous rotation instruments have a higher tendency for canals transportation and aberrations, especially with larger curvatures. Reciprocating files were faster than continuous rotation files in shaping simulated root canals in resin blocks.